EFFECT OF BABY MASSAGE ON BABY WEIGHT AGED 0-6 MONTHS - Deviana Ramdhawati Hasanah; Etin Rohmatin; Herni Kurnia (Poltekkes Kemenkes Semarang, 2019)
Background: Infancy is a golden period as well as a critical period of development. It is said to be a critical period because at this time the baby is very sensitive to the environment and is said to be a golden period because the time is very short and cannot be repeated again. Stimulation in infancy is very necessary to stimulate growth and development. Baby massage is an activity carried out by parents or caregivers of the baby as an act of stimulating the growth and development of the baby Purpose : The aim of the study is to determine the effect of baby massage on infants’ weight aged 0-6 months in working area of Cibeureum Public Health Center in Tasikmalaya Method: Pre-experimental design with one group pretest-posttest design approach was applied. Total respondents were 29 infants, obtained using purposive sampling technique. Data analysis used univariate analysis and bivariate analysis with the Spearman correlation test. Results: The results showed, the p-value was 0.05 which was considered as more than α (0,000). It can be stated that Null hypotheses were accepted, there was no effect onof baby massage on infants’ weight. Conclusions: This study did not support the effect of baby massage towards babies’ weight. However, baby massage is remain suggested in order to improve emotional relationship between the parent and the baby. Future studies need to be conducted regarding baby massage combined with other treatment that might help infants’ growth